2016
DOI: 10.1590/s1678-9946201658025
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans PROTEIN PROFILE CHANGES IN RESPONSE TO THE BUTANOLIC EXTRACT OF Sapindus saponaria L.

Abstract: SUMMARYCandida albicans is an opportunistic human pathogen that is capable of causing superficial and systemic infections in immunocompromised patients. Extracts of Sapindus saponaria have been used as antimicrobial agents against various organisms. In the present study, we used a combination of two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) to identify the changes in protein abundance of C. albicans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
7
0
5
Order By: Relevance
“…Unfortunately, Onipede et al27 in Nigeria found high and multiple resistance patterns of GBS isolates to different antibiotics in their study, where 100% of isolates were resistant to penicillin G, ampicillin, and clindamycin and 64.7% and 70.6% were resistant to erythromycin and vancomycin, respectively. In Brazil, a lower degree of resistance was detected by Melo et al,28 where all of the GBS isolates were susceptible to penicillin and vancomycin. They also reported that 8.1% of isolates was resistant to erythromycin and 5.9% resistant to clindamycin 28…”
Section: Discussionmentioning
confidence: 85%
“…Unfortunately, Onipede et al27 in Nigeria found high and multiple resistance patterns of GBS isolates to different antibiotics in their study, where 100% of isolates were resistant to penicillin G, ampicillin, and clindamycin and 64.7% and 70.6% were resistant to erythromycin and vancomycin, respectively. In Brazil, a lower degree of resistance was detected by Melo et al,28 where all of the GBS isolates were susceptible to penicillin and vancomycin. They also reported that 8.1% of isolates was resistant to erythromycin and 5.9% resistant to clindamycin 28…”
Section: Discussionmentioning
confidence: 85%
“…Samples were resuspended with lysate buffer (7 M urea, 2 M thiourea, 40 mM DTT, 1 mM PMSF [24]) and were sonicated (1 s/1 s intervals, 80 W power) for 3 min. Cell debris was removed by centrifugation at 3000 g for 5 min at 4°C.…”
Section: Proteome Analysismentioning
confidence: 99%
“…For proteome analysis, Candida cells recovered from kidney and plated on SDA were collected and centrifuged for 5 min at 3,000 rpm. The pellet was washed three times with ultrapure water and resuspended in 1,100 μl of buffer containing 7 M urea, 2 M thiourea, and 40 mM DTT (Fiorini et al, 2016). Then, the suspension was sonicated (30 bursts of 10 s ON, 30 s OFF at 100% amplitude).…”
Section: Methodsmentioning
confidence: 99%